Lutte De Leadership Feminin Au Pouvoir Et (Re) Structuration De Rapports Sociaux De Sexe En Province Orientale - Bibiche Liliane Salumu Laumu Omeyaka (European Scientific Journal, ESJ, 2018)
This paper focuses on the subversive and performative gender dimension of the emergence of women politicians in post-Mobutu Oriental Province. The ambition of these women political leaders, in a bid to maintain their status as women's elite, derives its livelihood in the implementation of their ability. This capability creates social change through social deconstruction of gender roles in the society structural transformations known as neo “patriarchal" and also in the heterosexual relationship (man-woman) and homosexual relationship (women-women) known as "transformations interactionists". From this perspective, these elites are indeed agents of change for the welfare of women in their province. This way of acting was being made from them women's elites of conviction. The opposite, however, were also observed when some of them resigned themselves from being able to break the glass wall sheltering the inequalities between the sexes for others especially political purposes. They are selective in their commitment. In this case, it is women’s elites of convention serving, most often times, as a gateway to politics. This entrepreneurship of women political leaders causes the political subsystem to change into neo-patriarchalism. It is through the narratives of life coupled interviews that we have managed to highlight the particularities of these women determined to forge a personality in a cultural, social, and political space that is very constraining for them.